Impact of Gas Masks on the Work of Breathing and Breathing Pattern in Subjects With Stable COPD. - Bourassa, Stéphane; Bouchard, Pierre-Alexandre; Lellouche, François (Respiratory Care, 2019)
BACKGROUND: The gas mask constitutes the main respiratory protective equipment in a chemical, biological, radiological, or nuclear environment. The aim of the study was to evaluate the impact of the gas mask on respiratory pattern, gas exchange, and indexes of respiratory effort in patients with moderate to severe stable COPD. METHODS: Crossover evaluation with 3 randomized- order, 10-min conditions: at rest and with and without a gas mask using 2 different filtered cartridges, each with a distinct inspiratory resistance (cartridge A = 3.5 cm H2O; cartridge B = 2.2 cm H2O, both at 1 L/s). The study involved 8 subjects with COPD, and breathing patterns, indexes of respiratory effort, and capillary blood gases were evaluated. Comparisons of these parameters were made between the tested conditions. RESULTS: Mean subject age was 69 y, and mean FEV1 = 1.3 L (47% predicted). Short-term utilization of the gas mask was associated with a significant increase in the indexes of effort in comparison to baseline without a mask. The esophageal product-time product significantly increased in comparison with baseline (cartridge A = 281 ± 65 cm H2O/s/min, cartridge B ± 253 ± 47 cm H2O/s/min, and baseline = 184 ± 46 cm H2O/s/min, P < .001). There were negligible changes in the breathing pattern and gas exchange. CONCLUSIONS: Indexes of respiratory effort increased slightly in subjects with stable COPD while using a gas mask. This effect was likely related to increased inspiratory resistance when the mask was worn. These data are reassuring for the potential short-duration use of such protection for patients with moderate to severe COPD.